STRENGTHENING TEACHER COMPETENCY IN UTILIZING EDUCATIVE DEVICES IN PAUD SEROJA DESA ARA PAYUNG - Faisal, Faisal; Ray, Damaiwaty; Simbolon, Naeklan; Lova, Stelly Martha (Universitas Negeri Medan, 2018)
AbstractThis mentoring program aims to improve teacher competency in utilizing educational teaching aids (APE) at the PAUD Seroja Desa Ara Payung. The stages of activities carried out through the mentoring program include: (1) mentoring the preparation of the Learning Implementation Plan (RPP) in PAUD, (2) mentoring on how to make educational teaching aids in PAUD, (3) mentoring how to use teaching aids in PAUD learning, (4) simulation in the form of lesson study on the use of educational teaching aids in PAUD, (5) open class/real teaching using educational teaching aids in PAUD learning, (6) monitoring and evaluation, and (7) follow-up. Based on the stages of the activities carried out, teacher competency can be improved in terms of formulation of the lesson plan, the making of educational teaching aids, and their effective use in learning in PAUD. Specific targets and outcomes generated through the mentoring program include: (1) the module for making educational teaching aids in PAUD learning, (2) educational teaching aids based on themes in PAUD learning, (3) teachers using educational teaching aids that will documented in the form of learning videos, (4) scientific publications in online ISSN journals and mass media. The method of implementing assistance is carried out through several stages, including (1) preparation, (2) implementation, (3) monitoring and evaluation, and (4) follow-up. With the method used, it is able to improve teacher competencies related to the use of educational teaching aids in the learning process effectively in PAUD.Keywords: Educative Teaching Aids, Teacher Competence, PAUD.